Organizational Well-Being at Government Corporation - Syahida Tiara Rinanda; Maya Rosmayati Ardiwinata; Yus Nugraha (Humanitas (Jurnal Psikologi), 2019)
Every company needs a good synergy between the organization and employees so that the company can progress and develop. It is important to build an organizational environment that promotes well-being of its members in the organization, by creating an effective, reflective and affective environment so that employees can work efficiently organized and responsible for achieving organizational goals.This study will describe organizational well-being that owned by one of the government-owned companies that produce vaccines, refer to how the company provides an effective, reflective, and affective environment (Prilleltensky & Prilleltensky, 2006), with a total of 550 permanent employees from all directorates in the company.The results of this study describe organizational well-being in the company shows that employees have a fairly positive perspective in looking at effective environment conditions to support organizational goals, reflective to be able to improving themselves through evaluation, and affective in mutual support and warm conditions. Keywords: Organizational Well-Being, Effective Environment, Reflective Environment, Affective Environment